Identification and functional analysis of two serotonin N-acetyltransferase genes in maize and their transcriptional response to abiotic stresses - Guo, Xiaohao; Ran, Le; Huang, Xinyu; Wang, Xiuchen; Zhu, Jiantang; Tan, Yuanyuan; Shu, Qingyao (Frontiers in Plant Science, 2024)
Melatonin, a tryptophan-derived indoleamine metabolite with important roles in plant growth and defense, has recently been regarded as a new plant hormone. Maize is one of the most important cereal crops in the world. Although the melatonin receptor gene, ZmPMTR1, has already been identified, the genetic basis of melatonin biosynthesis in maize has still not been elucidated. Serotonin N-acetyltransferase (SNAT) is the enzyme that converts serotonin to N-acetylserotonin (NAS) or 5-methoxytryptamine (5MT) to melatonin in Arabidopsis and rice, but no SNAT encoding gene has been identified yet in maize. In this study, we first identified three maize SNAT genes, ZmSNAT1, ZmSNAT2, and ZmSNAT3, through bioinformatics analysis, and demonstrated that ZmSNAT2 was present in only eight of the 26 cultivars analyzed. We then determined the enzyme activity of ZmSNAT1 and ZmSNAT3 using their recombinant proteins through in vitro assay. The results showed that both ZmSNAT1 and ZmSNAT3 could convert serotonin to NAS and 5-MT to melatonin. Recombinant ZmSNAT1 catalyzed serotonin into NAS with a higher catalytic activity (Km, 8.6 mM; Vmax, 4050 pmol/min/mg protein) than ZmSNAT3 (Km, 11.51 mM; Vmax, 142 pmol/min/mg protein). We further demonstrated that the 228 th amino acid Tyr (Y228) was essential for the enzymatic activity of ZmSNAT1. Finally, we revealed that the expression of ZmSNAT1 and ZmSNAT3 varied among different maize cultivars and different tissues of a plant, and was responsive to drought and heat stresses. In summary, the present study identified and characterized the first two functional SNAT genes in maize, laying the foundation for further research on melatonin biosynthesis and its regulatory role in plant growth and response to abiotic stresses.